The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4103/ijo.ijo_1800_18
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and immunohistochemistry correlation in a case of Vogt-Koyanagi-Harada disease

Abstract: Vogt-Koyanagi-Harada (VKH) disease is a systemic disorder causing bilateral panuveitis. Histopathological documentation along with molecular diagnostic evidence in VKH eye is a rarity. We present a 46-year-old woman with VKH with several ocular complications and subsequently enucleation of the right eye was done because of painful blind eye. Patient had clinical complications of VKH and some of the complications were observed in histopathology. Pathology of the case showed nongranulomatous uveitis, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Several studies have indicated that VKH disease is associated with histopathological changes in the choroid 12,13 . Infiltration of plasma cells and lymphocytes and the presence of CD3-positive cells in the choroid www.nature.com/scientificreports/ have been observed in HE and immunohistochemistry sections from human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that VKH disease is associated with histopathological changes in the choroid 12,13 . Infiltration of plasma cells and lymphocytes and the presence of CD3-positive cells in the choroid www.nature.com/scientificreports/ have been observed in HE and immunohistochemistry sections from human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed cytotoxic T-cells in the eye ball specimen of Eales disease. T cell mediated immunologic reaction has been found in Behcet’s disease [ 4 ], Vogt Koyanagi Harada disease [ 5 ] and sympathetic ophthalmia [ 6 ]. Our study indicates in active stage of Eales disease, immunomodulatory therapy with T cell inhibitors may be effective.…”
Section: Discussionmentioning
confidence: 99%
“…4 Department of Uvea, Sri SankaradevaNethralaya, Guwahati, Assam, India. 5 Sankara Nethralaya Referral Laboratory, Tamil Nadu, Chennai, India.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…Hyperpigmented areas in atrophic patch are due to the proliferation of RPE, rarely associated with subretinal neovascularization [33]. Immunological markers like CD3 and CD20 with increased T cell involvement have been found in cases of VKH syndrome [34].…”
Section: Histopathological Featuresmentioning
confidence: 99%